Islamic Family Law Perspective on Marrying Pregnant Women - Anfasa, Farid; Ja’far, A. Kumedi (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2024)
Background. Sexual intercourse between a man and a woman without a valid marriage contract is called zina. Zina does not differentiate between a girl, a man, a husband or a widow, a wife or a widower. Islamic law strictly forbids zina, never even approaching zina. One of the consequences of zina is pregnancy outside of marriage.. Aims. This article examines pregnant marriage from the perspective of Islamic law in the four imams of the school of thought, and the Compilation of Islamic Law. Method. The study uses a normative legal approach. Results. Pregnant marriage is a marriage with a woman who is pregnant outside of marriage, either married to the man who impregnated her or to the man who did not impregnate her. The Marriage Law only implicitly regulates the marriage of pregnant women, namely in Article 2 paragraph (1). The Compilation of Islamic Law regulates the marriage of pregnant women in Article 53. The differences of opinion among scholars regarding the marriage of pregnant women due to adultery do not bring blessings to the community. The Compilation of Islamic Law states that children resulting from adultery legally do not have a kinship relationship with their father, even though the father formally acknowledges and legitimizes that the child is his own child. They do not have the intended relationship, be it family relationships, guardianship in marriage or inheritance issues. The child only has a bloodline relationship with his mother.